FOREST MANAGEMENT PLAN FOR IMPLEMENTATION OF A PILOT REDD+ PROJECT FOR MASITO COMMUNITY FOREST RESERVE, KIGOMA, TANZANIA FOR 2012-2017: REVIEW OF PREVIOUS MANAGEMENT PLAN - Nzunda, Emmanuel F. (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation/Background: Forest management planning is an important condition for ecologically sustainable and economically efficient forest use. The current paper presents review of previous forest management plan for implementation of a pilot REDD+ project for Masito Community Forest Reserve, , Tanzania for the period 2012-2017. Method: The work mainly involved review of relevant documents enriched by discussions with project management. Results: The description of the review is presented under twelve major sections, namely: 1. of previous forest management plan document; 2. of the previous forest management plan; 3. in implementing the previous forest management plan; 4. encountered during the implementation of the previous plan; 5. that affected the implementation of the previous forest management plan; 6. of existing forest resources; 7. reserve management activities; 8. resources for forest reserve management; 9. adjacent communities; 10. and initiatives for revenue generation; 11. linkages and co-operation, and; 12. resources for management of the forest reserve. Conclusions: The review was the basis for the activities planned for the forest for 2012-2017. Also, the review should be used as baseline information for assessment of achievement of the planned activities.